Analisis Pernyataan Badan Narkotika Nasional terhadap Efek Pembakaran Pemusnahan Barang Bukti Narkoba di Lingkungan Masyarakat - Robinson Robinson; Sania Marla Febrina Br Pelawi; Yolanda Anastasya Sembiring (Verdict: Journal of Law Science, 2026)
This research analyzes the statements made by the Indonesian National Narcotics Agency regarding the safety of the burning destruction of narcotics evidence and its effects on public health. The issues examined include the safety of smoke produced from narcotics burning, the protection of public health and the right to public information, as well as the application of the precautionary principle and state responsibility in environmental protection. This research employs a descriptive analytical normative juridical method using statutory, conceptual, and case approaches. The findings show that statements claiming that the smoke produced from the burning process is safe to inhale are not supported by independent scientific studies or publicly accessible air quality test results. The burning of synthetic narcotics has the potential to produce hazardous substances such as carbon monoxide, dioxins, and furans that may endanger public health and the environment. This research also identifies a legal vacuum regarding emission control standards and public health protection in the process of burning narcotics evidence. Destruction practices conducted without independent risk assessments and without the involvement of health authorities indicate non-compliance with the precautionary principle and state responsibility. Therefore, specific regulations governing the technical standards for narcotics destruction are necessary to ensure the protection of public health and the environment.